2018
DOI: 10.1016/j.healthpol.2017.11.006
|View full text |Cite
|
Sign up to set email alerts
|

The importance of population differences: Influence of individual characteristics on the Australian public’s preferences for emergency care

Abstract: A better understanding of the public's preferences and what factors influence them is required if they are to be used to drive decision-making in health. This is particularly the case for service areas undergoing continual reform such as emergency and primary care. Accordingly, this study sought to determine if attitudes, socio-demographic characteristics and healthcare experiences influence the public's intentions to access care and their preferences for hypothetical emergency care alternatives. A discrete ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…Considering the heterogeneous responses to the incentives, creating and implementing differentiated policies that target different patient groups may work better. Again, the difference in preferences in the common illness and diabetes care conditions supports the idea that the demand for care is pivotal in this decision‐making process . Future policies should include varied strategies based on patients' different medical demands.…”
Section: Discussionmentioning
confidence: 85%
“…Considering the heterogeneous responses to the incentives, creating and implementing differentiated policies that target different patient groups may work better. Again, the difference in preferences in the common illness and diabetes care conditions supports the idea that the demand for care is pivotal in this decision‐making process . Future policies should include varied strategies based on patients' different medical demands.…”
Section: Discussionmentioning
confidence: 85%
“…Apart from being a strategic imperative as part of efforts to reduce avoidable hospitalisations and improve population health outcomes, the current study demonstrates that health consciousness influences decisions to access care and be influenced by previous experiences of health care. 14 Health consciousness is a distinct health attitudinal measure and the merit of including it in health research alongside other measures of individual characteristics of care has been established. 14 Nevertheless, the health consciousness of Australians has not previously been reported.…”
Section: Discussionmentioning
confidence: 99%
“…This study was undertaken as part of a larger project to engage the public in health-care decision-making. 14,15 Ethics approval was obtained from the Griffith University Human Research Ethics Committee (MED/10/12/HREC) and the Metro South Hospital and Health Service Research Ethics Committee (HREC/12/QPAH/330).…”
Section: Methodsmentioning
confidence: 99%
“…Paul Harris in his study, assessing the Australian public's preferences, found that patients' individual attributes have a great impact on prioritizing emergency patients. [ 30 ]…”
Section: Discussionmentioning
confidence: 99%